FRICTION PRESSURE PREDICTION OF SUPERCRITICAL CO2 TURBULENT FLOW IN A CONCENTRIC ANNULUS - Md. Uddin; Md. Nahid Hossan; Mim Mashrur Ahmed; Raihan Karal (Media Mesin)
This study uses a numerical approach to examine the visual axial pressure gradient and friction factor characteristics of supercritical CO2 turbulent flow in a concentric annulus. The Computational Fluid Dynamics (CFD) software package (FLUENT) was applied for the investigation. The inlet temperature varied from 31 to 110 °C at two operating pressures 9 MPa and 14 MPa. The effect of mass flow rate, annulus clearance, and shaft rotational speed on the pressure gradient and friction factor are investigated. The results show that the pressure gradient is non-linear and the friction factor changes abruptly near the critical point. The effect of mass flow rate and shaft rotational speed on the friction factor is found significant whereas the effect of clearance is insignificant. The friction factor for a given condition is found in the range 0.042-0.029. A one-and-a-half times increase in the friction factor was found when there was a two-time increase in the rotational speed. A satisfactory agreement is obtained between the results predicted by CFD (fluent) when compared with the results predicted by the Darcy Weisbach equation and the Moody diagram and then with the experimental. Hence the Darcy Weisbach equation and Moody diagram can be an effective means of determining the pressure and friction factor respectively for the supercritical CO2 turbulent flow application through the concentric annulus.